Radiofrecuencia en pacientes con parálisis de Bell. - Villacres Saltos, Deicy Alexandra (2024)
Facial paralysis is a condition at the level of the facial nerve, which can become inflamed or compressed. It is divided into central and peripheral. Central facial paralysis occurs at the brain level, but not at the nerve level, and is usually the result of a stroke. while peripheral paralysis causes denervation of the trunk of the facial nerve to the terminal branches of the face. Bell's palsy, a form of peripheral facial paralysis, causes complete loss of facial movement, with symptoms of muscle weakness and loss of sensation. The global incidence is 15 to 30 cases per 100,000 people, mainly affecting individuals between 15 and 60 years of age. Treatment includes corticosteroids, antivirals, analgesics and physical therapy techniques; due to the use of radiofrequency, electrotherapy, facial mimicry exercises and massages to improve circulation and muscle tone, achieving facial symmetry. The objective of this study is to determine the effects of radiofrequency as a treatment in patients with Bell's palsy through relevant scientific articles in order to speed up the recovery process of facial muscles. The research is bibliographic, articles were collected from different databases such as: PEDro, Scielo, Medline and Biomed Central Journal, where inclusion and exclusion criteria were used for selection. Finally, ten randomized clinical trial articles were identified to carry out the evaluation using the Physiotherapy Evidence Database scale. Radiofrequency has been shown to be an effective treatment for Bell's palsy, offering significant benefits in improving the functionality of facial muscles because the application of controlled heat through the use of the physical medium not only reduces pain, but also improves circulation and stimulates tissue regeneration.